2016
DOI: 10.1002/mawe.201600457
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites specifically penetrate and inhibit tumor cells

Abstract: A most important task in oncology today is the search for structures capable of specific targeting and inactivating the cancer stem cells determining the tumor growth. We describe the investigation of the ability of the synthesized hybrid nanocomplexes containing rare earth-based nanoparticles of GdYVO 4 : Eu 3+ orthovanadates, cholesterol and the hydrophobic luminescent dye DiI to visualize and inactivate the cancer stem cells of the Ehrlich carcinoma. The spectral analysis revealed an intracellular accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
1
0
3
Order By: Relevance
“…Our earlier studies have shown that hybrid nanocomplex is able to be integrated not more than into 10% of cells of total EC population and virtually to all the cells of isolated CD44 + fraction having the highest carcinogenic potential. This allows the use of hybrid nanocomplex in this modification (NPs + cholesterol + DiI) as a method of identifying local accumulation of nanocomplexes in cancer cells [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier studies have shown that hybrid nanocomplex is able to be integrated not more than into 10% of cells of total EC population and virtually to all the cells of isolated CD44 + fraction having the highest carcinogenic potential. This allows the use of hybrid nanocomplex in this modification (NPs + cholesterol + DiI) as a method of identifying local accumulation of nanocomplexes in cancer cells [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Попередні дослідження довели, що додавання холестерину до НЧ підвищує ефективність тарґетної протипухлинної дії сформованих НК [13,14,15]. Однак час взаємодії клітин з НК в цих дослідженнях був підібраний згідно з даними, одержаними на клітинах здорової печінки [16].…”
Section: вступunclassified
“…Абсолютно не виключене існування «альтернативних» механізмів реалізації протипухлинної дії НК. Як було встановлено у попередніх наших дослідженнях, оброблення клітин АКЕ гібридними НК приводило до формування пулу клітин пухлини з пониженим ступенем експресії генів плюріпотентности, в першу чергу, NANOG, що є ключовим у визначенні самопідтримки СРК [13]. В цілому, одержані результати доповнюють уявлення про механізми реалізації протипухлинної терапії гібридними НК на основі ортованадатів рідкісноземельних елементів і ті чинники, які можуть впливати на них.…”
Section: акенкunclassified
“…Нанокомплекси, що складаються з НЧ GdYEuVO 4 і холестерину, мають деякі переваги над іншими нанокомпозитами за умов їх використання при онкологічних захворюваннях. НЧ ортованадатів рідкісноземельних металів GdYEuVO 4 , які входять до складу НК, здатні не тільки інгібувати пухлинний рост, але й візуалізувати стовбурові ракові клітини [10,17,46]. Застосовані НК як потенційні протипухлинні препарати продемонстрували селективність щодо ракових клітин і низьку токсичність до здорових клітин [4,10].…”
unclassified